LAJU PERTUMBUHAN INTRINSIK Helopeltis antonii SIGN. PADA BUAH MENTIMUN SEBAGAI PAKAN ALTERNATIF - DJATNIKA K.; I. WAYAN LABA; W. R. ATMADJA (Jurnal Penelitian Tanaman Industri, 1998)
Intrinsic growth rate of Helopeltis antonii Sign. (Hemip- tera; Miridae) on cucumberfruit as an alternativefoodThe study on the intinsic rate of natural increase of Helopeltis antonii Sign. On cucumber ruit as an alternative food was conducted in the pest and disease Laboratory, Research Institute for Spice and Medicinal Crops Bogor rom January o June 1998. Helopeltis antonii is well known as the pest of cashew, cacao and tea The objectives of the experiment wee to study the reproduction rate and fecundity of H antonii. The insects were collected from the field of cashew tees in Bogor. A pair of newly emerged adult was eleased into a plastic jar containing cucumber fruit. The fruit was changed daily until the insects died. A newly emerged nymph was eaed individually in a plastic cup containing a peace of cucumber ruit which was renew every 2 days. Birch exponential equation: N,=No.e" was used for analyzing data. The results showed that intrinsic rate (r) of//, antonii was 0.106. Net eproduction rate (Rn) was 18.952 times for each generation. The generation period was 27.747 days. The value of finite rate of increase was 1.1 12 times/day. After one month and two months a pair of insect would multiply to 24 and 578 pairs, espectively.